Snapshots of men and women in interaction: an investigation of stereotypes in print advertisement relationship portrayals - Zotos, Yorgos; Tsichla, Eirini (My University, 2014)
This paper pursues a line of enquiry into gender stereotypes in advertising, by the exclusive examination of images of men and women in interaction. Drawing evidence from Cypriot magazine advertisements, the study employs the coding scheme developed by Goffman. The findings indicate that when males and females are framed together in advertisements, the presence of gender clichés is evident even when transcribed in a subtle fashion. Contrary to previous research, joint portrayals emphasize the relative size of men and women and men’s status superiority. Conversely, females tend to perform inferior roles, occupy less space in the advertisements, wear light clothing, and adopt postures that suggest subordination and withdrawal more often than men. In addition, differences in the degree of stereotyping were detected as general audience magazines contain advertisements with less traditional patterns compared to women’s and men’s magazines. The type of endorsed product further influences the depiction of the models, as females endorsing hedonic products are more likely to be captured in a stereotypical fashion than males.
Keywords: Stereotypes; Stereotypes; Gender; Content analysis